2003
DOI: 10.1021/np0304114
|View full text |Cite
|
Sign up to set email alerts
|

Ponicidin and Oridonin Are Responsible for the Antiangiogenic Activity of Rabdosia rubescens, a Constituent of the Herbal Supplement PC SPES

Abstract: Antiangiogenic activity has been identified in an aqueous EtOH extract of Rabdosia rubescens, a component of the dietary supplement PC SPES. Bioassay-guided fractionation using a novel in vitro human endothelial cell-based assay for angiogenesis afforded the diterpenoids ponicidin (1) and oridonin (2), with significant antiangiogenic activity at subcytotoxic concentrations, suggesting that these constituents may strongly contribute to the demonstrated clinical efficacy of PC SPES as a treatment for advanced pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…It exhibited an even pseudomolecular ion peak at m/z 514 [M+Na] + in the ESIMS spectrum, suggesting that it might be a N-containing compound. The HRESIMS data (m/z 514.2430 [M+Na] + , calcd for 514.2416) further confirmed this assumption, giving rise to the molecular formula C 26 H 37 NO 8 . Its strong IR absorptions at 3387 and 1711 cm À1 suggested the presence of hydroxyl and carbonyl groups.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…It exhibited an even pseudomolecular ion peak at m/z 514 [M+Na] + in the ESIMS spectrum, suggesting that it might be a N-containing compound. The HRESIMS data (m/z 514.2430 [M+Na] + , calcd for 514.2416) further confirmed this assumption, giving rise to the molecular formula C 26 H 37 NO 8 . Its strong IR absorptions at 3387 and 1711 cm À1 suggested the presence of hydroxyl and carbonyl groups.…”
Section: Resultsmentioning
confidence: 59%
“…7 Recently, pharmaceutical study showed that oridonin and ponicidin had significant antiangiogenic activity. 8 More recently, these two compounds were found to be potent inhibitors of NF-kB transcription activity and the expression of its downstream targets, COX-2 and inducible nitric-oxide synthase. 9 With an aim to isolate more potent and selective NF-kB inhibitors, we further systematically reinvestigated the chemical constituents of I. rubescens, and 31 7,20-epoxy-ent-kauranoids, including 12 new ones, hebeirubescensins A-L (1-12), were isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that oridonin was one of the most important antitumor active ingredient of Rabdosia rubescens (33)(34)(35)(36). Our previous studies showed that oridonin could arrest the cell cycle in G 2 /M phase in human gastric cancer SGC-7901 cells (3).…”
Section: Discussionmentioning
confidence: 99%
“…Thus baicalin, the main agent of Scutellaria baicalensis, has been demonstrated to inhibit proliferation in prostate and myeloblastic/promyelocytic leukaemia cell lines (15) or breast cancer cell lines (16), respectively. Rabdosia rubescens inhibits growth of breast cancer cells as well as angiogenesis (17), the active agents have been identified as ponicidin and oridonin (18).…”
Section: Discussionmentioning
confidence: 99%